2001
DOI: 10.1161/hq0701.092104
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Protein Expression in Vascular Smooth Muscle Cells In Vitro and In Vivo Is Regulated Through Phosphatidylinositol 3-Kinase and Mammalian Target of Rapamycin

Abstract: Abstract-Cell cycle progression represents a key event in vascular proliferative diseases, one that depends on an increased rate of protein synthesis. An increase in phosphatidylinositol 3-kinase (PI 3-kinase) activity is associated with vascular smooth muscle cell proliferation, and rapamycin, which blocks the activity of the mammalian target of rapamycin, inhibits this proliferation in vitro and in vivo. We hypothesized that these 2 molecules converge on a critical pathway of translational regulation that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(82 citation statements)
references
References 40 publications
7
75
0
Order By: Relevance
“…phosphorylation), in parallel to its role in control of cell growth. Cell growth and cell cycle progression would therefore be coordinated by virtue of sharing a common upstream regulator, mTOR rapamycin inhibiting the expression of various cell cycle control proteins (Braun-Dullaeus et al, 2001), it not clear whether the observed effect is a direct effect of mTOR inhibition or whether it is an indirect secondary consequence of a delay in cell cycle progression. Certain cyclins may also be able to function as cell growth drivers, as it is reported that in Drosophila, cyclin D/ cdk4 complexes promote cell growth in addition to their role in driving cell cycle progression Meyer et al, 2000).…”
Section: Rheb An Activator Of Tor That Is Inhibited By Tsc2mentioning
confidence: 99%
See 1 more Smart Citation
“…phosphorylation), in parallel to its role in control of cell growth. Cell growth and cell cycle progression would therefore be coordinated by virtue of sharing a common upstream regulator, mTOR rapamycin inhibiting the expression of various cell cycle control proteins (Braun-Dullaeus et al, 2001), it not clear whether the observed effect is a direct effect of mTOR inhibition or whether it is an indirect secondary consequence of a delay in cell cycle progression. Certain cyclins may also be able to function as cell growth drivers, as it is reported that in Drosophila, cyclin D/ cdk4 complexes promote cell growth in addition to their role in driving cell cycle progression Meyer et al, 2000).…”
Section: Rheb An Activator Of Tor That Is Inhibited By Tsc2mentioning
confidence: 99%
“…Rapamycin inhibits the increased proliferation and migration of vascular smooth muscle cells that occurs after injury (Poon et al, 1996;Gallo et al, 1999;Roque et al, 2000) and also induces their differentiation back toward a more mature phenotype (Martin et al, 2003). The injury-induced expression of several cell cycle regulatory proteins is inhibited by the in vivo administration of rapamycin to rats, suggesting a mechanism for the antirestenotic effect of rapamycin on proliferation (Braun-Dullaeus et al, 2001). After successful clinical trials, rapamycin (sirolimus) is now FDA approved for use on drug-eluting stents to inhibit restenosis after coronary artery intervention (Morice et al, 2002;Moses et al, 2003).…”
Section: A Role For Tor In Other Human Disease Statesmentioning
confidence: 99%
“…At the plasma membrane, Akt is activated, in part through phosphorylation by phosphoinositide-dependent kinase-1 and PIP3. Akt is then capable of phosphorylating a number of downstream targets, such as mammalian target of rapamycin (mTOR) (33)(34)(35). Mitogen-activated protein kinase pathway The mitogen-activated protein kinase (MAPK) pathway ( Figure 3) is a second intracellular signalling pathway that may be initiated by TKR activation; Ras is a membrane G-protein that transmits the signal received by the TKR at the cell surface to activate the intracellular MAPK pathway.…”
Section: Early Cell Cycle Progression (G0/g1/s Phase)mentioning
confidence: 99%
“…We showed previously that phosphoinositide 3-kinase (PI3K) is essential for the VSMC cycle (3), and this enzyme was implicated recently in restenosis (4). PI3Ks make up a large family of lipid kinases, but class I PI3Ks are the most well known (5-7).…”
mentioning
confidence: 99%